Merits and Demerits of Incorporating Learning Style into EFL Classroom Instruction: A Literature Review - Pratiwi, Wahyuni; sabilah, fardini; Kurniawati, Sri; Nurlestari, Khofifah; Mujtahidah H, Bidayatul; Merlinda, Riza; Hidayatullah, Taufik (Universitas Pendidikan Mandalika, 2024)
The concept of learning styles proposing the alignment of teaching methods and individual learning styles to enhance learning outcomes has gained popularity among English language teachers. However, numerous studies have debunked the concept by exposing weaknesses in the instruments used to measure learning styles and the underlying hypothesis. Therefore, there is a need for more research focusing on the merits and demerits of implementing learning styles theory in EFL classroom instruction. This study is presented to provide empirical understanding into the issue by presenting the latest research findings and providing recommendations for EFL teachers. To achieve this aim, the researchers conduct a literature review by collecting data from various document references and theories supporting the research. The literature was collected from journal articles published in the last five years, from 2018 to 2023. Based on the review, some studies confirmed that tailoring teaching methods to individual learning styles contributed to improved learning outcomes for EFL students. Conversely, other research has shown no significant or consistent correlation between teaching-specific learning styles and students' achievement. To address this disparity, the present study suggested that foreign language teachers maximize teaching-learning by considering several factors rather than one, such as teaching strategy, students' interpersonal orientations, knowledge, students' background, and interests. Teachers can balance instructional approaches, methods, and activities and apply various teaching strategies to reach all learners.